Um jogo híbrido como estratégia de leitura para a obra clássica Memórias Póstumas de Brás Cubas, de Machado de Assis - Birck, Rafaela Lermen (2023)
This study is part of the Management of Network Educational Technologies research line, of the Postgraduate Program in Network Educational Technologies, at the Federal University of Santa Maria, in the Professional Master's modality. The theme of the work is the use of games to teach Literature in the 2nd year of High School, focusing mainly on classic works, in order to promote students' interest in Literature classes and, mainly, in classic books. We sought to analyze the extent to which the use of games can impact reading development, as well as contribute to teaching-learning in the classroom. The products created to achieve these objectives are: a hybrid game, based on Machado's work Memórias Póstumas de Brás Cubas, and a didactic sequence, consisting of the necessary steps for the teacher to use the game in class. In this way, we sought to reflect on the use of technologies in the classroom, and the role of the teacher as a mediator of knowledge. The target audience were 2nd year high school students at Colégio Estadual Tancredo Neves, in Santa Maria - RS. The methodology chosen was Design Science Research (DSR), with a qualitative approach, involving readings on the topic, choosing the object of study and choosing the school knowledge that was researched, also going through evaluation stages and the application of the game. The evaluations and the application itself constituted the results explained in this work. The results of this work were produced through a diagnostic questionnaire, followed by the application of the game and, finally, the evaluation questionnaire. The results demonstrated that there is a very large gap in relation to teaching-learning mediated by technologies in the Literature discipline and, furthermore, that there is an extreme need for innovation and renewal in classes, as arousing students' interest in this discipline is increasingly difficult. Therefore, it becomes increasingly necessary to expand actions in this regard.